2014
DOI: 10.1139/cjpp-2014-0035
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and socio-economic conditions as factors contributing to chronic stress in sub-Saharan African communities

Abstract: Stress is known to contribute to overall health status. Many individuals in sub-Saharan Africa are believed to be stressed about their employment, income, and health. This study aimed to investigate hair cortisol as a biomarker of chronic stress in settlement communities in Kenya. Hair samples were collected from 108 volunteers from settlement communities in Kenya. An enzyme-linked immunosorbent assay technique was used to measure hair cortisol concentrations. In parallel, a health survey was completed. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 41 publications
2
20
0
1
Order By: Relevance
“…The results are in line with previous studies focusing on traditional cortisol specimens from saliva and blood that have reported lower income to be associated with disturbed cortisol regulation ( Cohen et al, 2006 , Dowd et al, 2009 ). It is also consistent with a relatively recent study showing that lower income as a measure of deprivation was related to higher hair cortisol levels in women from sub-Saharan African communities ( Henley et al, 2014 ). The present study adds to these findings by showing a clear dose-response relationship between income and hair cortisol.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results are in line with previous studies focusing on traditional cortisol specimens from saliva and blood that have reported lower income to be associated with disturbed cortisol regulation ( Cohen et al, 2006 , Dowd et al, 2009 ). It is also consistent with a relatively recent study showing that lower income as a measure of deprivation was related to higher hair cortisol levels in women from sub-Saharan African communities ( Henley et al, 2014 ). The present study adds to these findings by showing a clear dose-response relationship between income and hair cortisol.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between financial status (income) and hair cortisol is not well studied. The only study to date reported elevated hair cortisol in participants earning less than the minimum wage in different communities in sub-Saharan Africa ( Henley et al, 2014 ). Some mixed evidence also exists for the effect of parental income on children’s hair cortisol levels ( Bosma et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…HCC increases in relation to objective psychosocial stressors such as unemployment (Dettenborn et al, 2010) and negative life events (Staufenbiel et al, 2014). For example, a recent study in Kenya reported higher HCC in those who made less than minimum wage and those who reported feeling physically unsafe when collecting water (Henley et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Though the literature focuses on water insecurity, sanitation access presents similar psychosocial risks, particularly for women and girls. In Kenya, Henley and colleagues studied hair cortisol concentrations as a biomarker for chronic stress, finding that concentrations were significantly higher in women who reported feeling unsafe while collecting water or accessing sanitation [ 4 ]. In a study of mental health in urban slums in Bangladesh, Gruebner, et al found that elements of the built environment including access to a better toilet facility were significantly associated with high quality of life scores (WHO-5 scores) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%